2002
DOI: 10.1159/000064683
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ST-T-Segment Changes with Markers of Hemostasis in Patients with Acute Coronary Syndromes

Abstract: Background: Disturbance of the hemostatic and the inflammatory system plays an important role in the pathophysiology of acute coronary syndromes (ACS). Their markers have been shown to predict further coronary events in patients with ACS. The prognostic value of the admission electrocardiogram (ECG), which is commonly used to evaluate ischemia, was studied previously. We investigated the correlation between serum markers of the hemostatic/inflammatory system and ECG changes in ACS. Methods: A standard 12-lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Although the population considered in these studies was heterogeneous in comparison with our patients (patients were taking aspirin, had high levels of troponin I on admission, and determinations of CRP over 6 h of the onset of chest pain were included), from these reports, it was possible to observe a trend to higher CRP values in patients with unstable angina pectoris and ischemic ST-T wave abnormalities compared with patients without ECG changes. Ehlers et al [18] also demonstrated a significant association between high fibrinogen and thrombin-antithrombin III complex levels and patients with ST-T changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the population considered in these studies was heterogeneous in comparison with our patients (patients were taking aspirin, had high levels of troponin I on admission, and determinations of CRP over 6 h of the onset of chest pain were included), from these reports, it was possible to observe a trend to higher CRP values in patients with unstable angina pectoris and ischemic ST-T wave abnormalities compared with patients without ECG changes. Ehlers et al [18] also demonstrated a significant association between high fibrinogen and thrombin-antithrombin III complex levels and patients with ST-T changes.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies evaluated the possible association between serum CRP levels and ECG patterns [17, 18]. Although the population considered in these studies was heterogeneous in comparison with our patients (patients were taking aspirin, had high levels of troponin I on admission, and determinations of CRP over 6 h of the onset of chest pain were included), from these reports, it was possible to observe a trend to higher CRP values in patients with unstable angina pectoris and ischemic ST-T wave abnormalities compared with patients without ECG changes.…”
Section: Discussionmentioning
confidence: 99%
“…The type of anaesthesia may modulate haemostatic activation [8, 14, 22, 23], which is thought to play a causal role in the aetiology of postoperative deep vein thrombosis and pulmonary embolism [8, 12, 13, 16]. Interestingly, in nonsurgical patients with unstable angina, a temporal relationship exists between systemic coagulation activation (fibrinogen level) and ST segment shifts, and intracoronary thrombus formation [7, 8, 24]. Until now, however, no attempt has been made to investigate the possible association of haemostatic activation with peri‐operative myocardial ischaemia and myocardial cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…The latter may be due to activation of platelets and blood coagulation with subsequent formation of intracoronary fibrin and microthrombosis [3–6]. In nonsurgical patients with an unstable pattern of angina, a temporal relationship exists between systemic thrombin activity and ST segment shifts [7, 8]. Because it is well known that major surgery, especially vascular, causes systemic coagulation activation [9–18], peri‐operative hypercoagulation might be associated with peri‐operative myocardial ischaemia and subsequent myocardial cell damage.…”
mentioning
confidence: 99%
“…It is a serine protease inhibitor (serpin), which inhibits the formation of thrombin. Stroke is associated with decreased AT-III activity and an increased in thrombin-AT-III complexes [11][12][13]. ApoC-I belongs to the apolipoprotein family.…”
Section: Discussion Of Biomarkersmentioning
confidence: 99%